2019
DOI: 10.1002/mame.201900412
|View full text |Cite
|
Sign up to set email alerts
|

Natural Silk Film for Magnesium Protection: Hydrophobic/Hydrophilic Interaction and Self‐Healing Effect

Abstract: Biodegradable implants are required in order to provide successful treatment of injuries. Temporary magnesium‐based implants with particular properties are needed in cases when it is desirable not only to maintain vital activity, but also to initiate the self‐healing process of damaged bones or tissues as well. Unfortunately, the use of magnesium alloys is limited due to the fast biodegradability of the applied material. The aim of this research is to improve the corrosion resistance of magnesium alloys by son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Another highly promising material which is biocompatible, provides high mechanical strength and has a unique structure is spider silk [94][95][96]. Zhang et al [97] have demonstrated the potential of a TENG based on recombinant spider silk.…”
Section: Natural Biodegradable Materialsmentioning
confidence: 99%
“…Another highly promising material which is biocompatible, provides high mechanical strength and has a unique structure is spider silk [94][95][96]. Zhang et al [97] have demonstrated the potential of a TENG based on recombinant spider silk.…”
Section: Natural Biodegradable Materialsmentioning
confidence: 99%
“…The FTIR spectra show the same characteristic polypeptide absorbance bands for The band observed at about 3300 cm −1 is due to stretching vibrations of the N−H bond, −OH groups of the proteins, and adsorbed water. 67,68 As mentioned earlier, the strong fluorescence ability of C-dot/ spider silk hybrids appears to be related to the presence of the −SCN group in its structure. To prove this, the spectra of the hybrid fibers (Figure 3A, orange) and pure powdered C-dots (Figure 3A, black) synthesized by the method described by Miao et al 64 were compared.…”
Section: ■ Introductionmentioning
confidence: 74%
“…This is typically accomplished by physical interaction or chemical interaction, as sketched in Figure 1. Most intrinsic recovery designs rely upon either reversible covalent bonds, such as Diels‐Alder reactions, [2–12] disulfide bonds, [13–17] boronate ester bonds, [18–21] and imine bonds, [22–24] or non‐covalent, including hydrogen bonds, [25–32] ionic, [33–37] and hydrophobic interactions, [38–40] host‐guest interactions, [41–45] π‐π stacking, [46–48] and metal coordination [49–54] or supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%